Epidemiological Analysis of the Frequency of Acute Respiratory Diseases and Diseases of the Circulatory System Using Medical Information Technologies - M. A. Papicheva; I. I. Yakushina (Эпидемиология и вакцинопрофилактика)
Relevance. Acute respiratory diseases (ARD) refer to mass infectious diseases, cause significant economic damage by provoking the development of diseases of the circulatory system, and the seasonal incidence of ARI is a predictor of mortality from cardiovascular diseases, which requires timely statistical accounting using the medical information system (MIS).The aim of the study was to quantitatively assess the risk of exposure to ARIs on the occurrence of diseases of the circulatory system using statistical data processing using MIS.Materials and methods. The epidemiological study was carried out in the design of a retrospective analytical cohort study of cases of temporary disability in the adult population, using statistical and analytical methods with the identification of a causal relationship using MIS, which provides the primary collection, storage, selection and grouping of data on the incidence of patients, with subsequent calculations of the relative risk and its 95% confidence interval.Results and discussion. Using the MIS, 88,735 cases of incapacity for work issued for the period from 2014 to 2019 were recorded and analyzed. Thanks to the reference architecture of the MIS, a sample of patients with acute respiratory infections was carried out, and their subsequent grouping according to the incidence rate into the main and control groups. The main group (frequently ill) was represented by patients who were ill more than 3 times per season, and the control group (rarely ill) was represented by patients who were ill from 1 to 2 times per season. The sample consisted of 4,980 patients, of which 1,461 were the main group and 3519 were the control group. A statistically significant relationship was revealed between the incidence of ARI and the development of angina pectoris with documented spasm (I20.1), chronic ischemic heart disease (I25.1), cerebrovascular disease (I67.9), atherosclerosis of the arteries of the extremities (I70.2), phlebitis and thrombophlebitis (I80), varicose veins of the lower extremities (I83), as well as hemorrhoids (I84).Conclusions. The introduction into the practice of MIS, which has a predominantly reference architecture, will optimize the epidemiological surveillance of infectious and non-infectious diseases, using the statistical registration of cases of temporary disability, mortality and hospitalization for taking timely and effective anti-epidemic and preventive measures.